Phyto-derived metal nanoparticles: Prominent tool for biomedical applications - P.R. Bhilkar; A.S. Bodhne; S.T. Yerpude; R.S. Madankar; S.R. Somkuwar; A.R. Daddemal-Chaudhary; A.P. Lambat; M. Desimone; Rohit Sharma; R.G. Chaudhary (Elsevier, 2023)
Nanoparticles (NPs), despite of very small in size have extraordinary power and functional ability, forms the backbone of nanomaterials science, and utilizes it in diverse fields. Many conventional methods can be employed for the fabrication of NPs, but it required either high energy with producing toxic byproducts that degrades an environment. Therefore, a green approach is needed to save an environment. Green methods provide the simple, straightforward, cost-effective and environmentally-safe approach for the NPs synthesis. Plant derived NPs, is one of the best and supreme methods with green and sustainable routes for preparation of NPs. As plant derived metal NPs gains the more attention due to their green synthesis approach and significant for biomedical appliances. In the present review, we concentrated on synthesis of plant derived metal NPs (Ag, Au, Cu, Ni, Zn and Ti) with their morphologies and biomedical applications. Also discussed the therapeutic applications and future perspective of plant derived metal NPs.